Neighbourhood social and physical disorders and adolescents’ stress in Kuala Lumpur, Malaysia / Fatemeh Hosseini - Fatemeh, Hosseini (2016)

(untitled)
Neighbourhoods are replete with high levels of social and physical phenomena that can generate a sense of hazard for the residents living in the area. Neighbourhood experiences and perceptions are more or less influenced by the social and physical circumstances present in the immediate living environment. Investigations of health conditions based on neighbourhood boundaries have been conducted since a century ago. However, in recent years, more attempts have been made to explore the associations between regions and health by focussing on the behaviours of the residents. Today, a variety of theoretical and analytical models have identified the direct and indirect pathways between neighbourhoods and mental health. One of these pathways is that of the neighbourhood which is believed to affect the mental health of the residents through the “neighbourhood disorders”. When a neighbourhood is disordered, it affects the residents’ and neighbourhoods’ conditions alike because there is no control over its maintenance. Neighbourhood disorders have been divided into two main components: “social disorders” and “physical disorders”. Since certain groups like adolescents are more vulnerable to the consequences of mental health, the main objective of this study was to assess the association between neighbourhood social and physical disorders as experienced and perceived by adolescents and their stress-level. A survey was conducted on 844 secondary school students who were aged between 13-15 years old in the Kuala Lumpur region of Malaysia between Januarys to May, 2014. The Adolescent Stress Questionnaire (ASQ) was used to measure their stress-level. Data were analysed in four stages: first, the adolescents’ experienced and perceived neighbourhood social and physical disorders and adolescents’ stress-level were examined separately through the factor analysis method. This method was used to classify the correlated variables. Second, the association between neighbourhood social and physical disorders and adolescents’ stress-level were assessed with other factors including (a) age, (b) gender, (c) iv socioeconomic status, (d) family functioning, and (e) individual preferences. This was determined by T-test and one way ANOVA. Third, multivariate regression was performed so as to analyse all the variables which include neighbourhood disorders, stress-level, age, gender, socioeconomic status, family functioning, and individual preferences. A final model was also introduced to define the association between neighbourhood disorders and adolescents’ stress. Finally, spatial autocorrelation analysis using ArcGIS software was performed to illustrate the disorders and stress across neighbourhoods. The results of this research showed that there was a positive association between neighbourhood disorders as experienced and perceived by adolescents and their stress-level. There was a statistically significant difference among adolescents’ individual preferences, their family functioning, and their socioeconomic status in the experiences and perceptions of neighbourhood disorders and stress. However, there was no statistically significant difference in different gender. The results of spatial analysis showed the hot spots in Kuala Lumpur city which reported high level stress and neighbourhood disorders. From the findings, it was concluded that neighbourhood social and physical disorders are significant enough to determine the stress-levels experienced among adolescents in the Kuala Lumpur region of Malaysia. It was recommended that urban planners and policy makers need to identify neighbourhoods that were more at risk of social and physical disorders in order to develop planning and building policies and mitigation actions which can further help the country to become healthier communities. Keywords: Mental Health, Urban Health, Neighbourhood Disorder, Urban Stress.